The experience of athletes with disabilities in mainstream sports: an interpretative phenomenological analysis - Jônatas Augusto Cursiol; Cristiano Roque Antunes Barreira (Motriz: Revista de Educacao Fisica, 2021)
Abstract Aim: Through reports of the athletes with disabilities interviewed, this study aimed to understand how the experiences lived in mainstream sports occur among people without disabilities. Methods: Husserl's classic phenomenology was the methodological framework adopted. The phenomenological interview was carried out with an intentional sample that included six athletes with some type of physical disability and later its recording was transcribed for the procedures of phenomenological reduction and intentional crossing to explain the meaning of what is experienced by these athletes in mainstream sport. Results: Five categories essentially describe how these experiences occur: operational body barred in the world; shaping the movement; the invisibility of disability; determination stimulus; and normalization of social relations in mainstream sports. These experiences correspond to a dynamic process in which each part does not necessarily follow the other. Conclusion: The experience in mainstream sports allowed the interviewees to improve their experience of capacity, self-efficacy, and recognition through the mutuality between self-perception and the expectation of acceptance by society.